Diseño de un sistema logístico en la empresa manufacturera cerámica lima « CELIMA » a través de la mejora continua - Figueroa Arroyo, Ana Claudia (2019)
The present project of applied research has as main problem the synchronization of information in the logistics chain of the company Ceramic Lima, the areas involved in this project are purchases, planning, production and storage, since the processes as a whole did not achieve the desired objective. From the manufacturing point of view, this project has logistic positions that will allow opting for critical analysis, since it shows diverse behaviors in the supply chain. In this way, the fluidity of information between each operating unit is of vital importance, adding the efforts of human capital, financial and natural resources. The motivation to carry out this research was given in order to demonstrate the theoretical knowledge learned throughout the academic training providing technical, operational and economic solutions. In this sense, this article presents the solutions for each eventuality that occurred along the logistics chain; evaluating the viability through an external and internal economic impact.